Dark cosmic rays - Ping-Kai Hu (Physics Letters B, 2017)
If dark matter particles have an electric charge, as in models of millicharged dark matter, such particles should be accelerated in the same astrophysical accelerators that produce ordinary cosmic rays, and their spectra should have a predictable rigidity dependence. Depending on the charge, the resulting “dark cosmic rays” can be detected as muon-like or neutrino-like events in Super-Kamiokande, IceCube, and other detectors. We present new limits and propose several new analyses, in particular, for the Super-Kamiokande experiment, which can probe a previously unexplored portion of the millicharged dark matter parameter space. Most of our results are fairly general and apply to a broad class of dark matter models.